2016
DOI: 10.1186/s12885-016-2097-4
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT as a prognostic biomarker in the era of molecular-targeting therapies: max SUVmax predicts survival of patients with advanced renal cell carcinoma

Abstract: BackgroundVarious molecular-targeting therapies have become available for the treatment of advanced renal cell carcinoma (RCC). Accurate prognostication is desirable for choosing the appropriate treatment for individual patients. 18F-2-fluoro-2-deoxyglucose positron-emission tomography/computed tomography (FDG PET/CT) is a non-invasive tool for evaluating glucose accumulation, which can be an index of biological characteristics of cancer. We prospectively evaluated FDG PET/CT as a prognostic indicator in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 25 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…SUVmax measured using PET could predict prognosis in various cancers, such as liver, kidney, pancreas, and breast cancer . In gynecological cancers, the SUVmax has also been reported to be useful for predicting the prognosis or the aggressiveness of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUVmax measured using PET could predict prognosis in various cancers, such as liver, kidney, pancreas, and breast cancer . In gynecological cancers, the SUVmax has also been reported to be useful for predicting the prognosis or the aggressiveness of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…SUVmax measured using PET could predict prognosis in various cancers, such as liver, kidney, pancreas, and breast cancer. [13][14][15][16] In gynecological cancers, the SUVmax has also been reported to be useful for Figure 5 Maximum standardized uptake value (SUVmax) by type of therapy in patients with complete remission (CR)/ partial remission (PR). In the patients treated with radiotherapy (RT) or concurrent chemoradiotherapy (CCRT) in those with CR/PR, the SUVmax was higher than in those treated with computed tomography (CT), but there was no statistically significant difference (P = 0.0857).…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT images were obtained using a single PET/CT system (Aquiduo 16; Toshiba Medical Systems, Tokyo, Japan) at the Yokohaha City University Hospital. The details about the condition of PET/CT examination and methods how to determine Standardized uptake value (SUV) were described in our previous report [10]. The highest SUV in an individual RCC lesion and the highest SUV in all RCC tumors of an individual patient were defined as SUVmax and max SUVmax, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We first found that pretreatment maximum SUVmax (max SUVmax), which was the highest SUV in all RCC lesions in individual patients, could predict the survival of patients with advanced RCC [9, 10]. Subsequently, we reported that patients with RCC whose max SUVmax decreased 20% or more one month after beginning TKI treatment showed long progression-free survival (PFS) [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, FDG PET/CT has shown some ability to predict survival in patients with advanced RCC. Nakaigawa et al demonstrated in 101 patients with advanced RCC (metastatic or locoregional disease) that the standardized uptake value (SUV) max on FDG PET/CT prior to systemic therapy independently predicted overall survival (OS) (8). Similarly, median SUV max on a baseline FDG PET/CT prior to systemic TT significantly predicted OS and progression free survival (PFS) in patients with advanced RCC (9).…”
Section: Imaging Biomarkersmentioning
confidence: 99%